Labour and development in East Asia : social forces and passive revolution - Gray, Kevin, 1973- (London : Routledge, 2015)
'Labour, Geopolitics and Development in East Asia shows that such inter-linkages between labour, geopolitical transformations, and states' developmental strategies have been much more central to East Asia's development than has commonly been recognised'--
Includes bibliographical references (pages 162-181) and index.
Keywords: Labor market -- East Asia; Economic development -- East Asia; East Asia -- Foreign economic relations